2017
DOI: 10.5603/fc.2017.0012
|View full text |Cite
|
Sign up to set email alerts
|

Zawał serca z uniesieniem odcinka ST u młodej kobiety z trombofilią złożoną

Abstract: StreszczenieChorą w wieku 31 lat przyjęto do kliniki z powodu silnego bólu w klatce piersiowej. Na podstawie obrazu klinicznego i wyników badań dodatkowych rozpoznano zawał serca z uniesieniem odcinka ST. W trybie pilnym wykonano koronarografię, a następnie rekanalizację zamkniętej gałęzi przedniej zstępującej z implantacją stentu uwalniającego zotarolimus, uzyskując poprawę kliniczną. Wśród czynników ryzyka miażdżycy stwierdzono nadciśnienie tętnicze i hipercholesterolemię. Ze względu na młody wiek chorej zle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Compared to the older population (over the age of 55), the main risk factors in younger women include smoking and obesity [4]. It was also observed that the V Leiden, prothrombin G20210A gene and MTHFR C667T mutation increases the risk of myocardial infarction and stroke, especially at an early age [5].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the older population (over the age of 55), the main risk factors in younger women include smoking and obesity [4]. It was also observed that the V Leiden, prothrombin G20210A gene and MTHFR C667T mutation increases the risk of myocardial infarction and stroke, especially at an early age [5].…”
Section: Discussionmentioning
confidence: 99%